Disability Sports Achievements Of Indonesian Special Schools Of Disability Students - Tesalonika Kurnianugraha; Erma Kumala Sari; Mohammad Anwar; Djoko Nugroho (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
This study aims to describe the achievements of disability sports students of Indonesian disability sports special schools and students with achievements in sports with disabilities in outstanding schools in peparpenas 2019. This study uses the qualitative research method. The subjects in this study were coaches and teachers of the Indonesian Special School for Disability Sports and Students with Achievements in Disability Sports in Outstanding Schools. Sampling techniques in this study used purposive sampling techniques. Data analysis techniques used are data reduction, data exposure, conclusion and verification. The results showed that (i) Physical as a form and can be seen by the naked eye, which is also a supporting element in improving the achievements of children with special needs in the sport of athletics consists of providing nutritional intake, and organ function; (ii) Psychological motivation, understanding the intellectuals of children with special needs, personality, and personality as one of the supporting achievements in the sport of athletics; (iii) Social support from friends, parents, family, teachers/trainers, and schools; and (iv) Supporting facilities and infrastructure, training, trainers, teachers, other skills, and organizational structure. The results of this study can be concluded that the achievements of sports students with disabilities in sports special schools with disabilities in Indonesia and students with sports disabilities in schools with achievement are physical, psychological, social, and support.